Madness in Linda Bouchard’s Black Burned Wood - Yri, Kirsten (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2009)
AbstractWith its images of paranoia, anger, resignation, and infantilism, Linda Bouchard’s Black Burned Wood may easily be aligned with musical representations of madwomen. The text, a cycle of eleven poems collected under the title “Sara Songs” takes the form of a rambling monologue in which Sara struggles to come to grips with her role in an unspecified but horrible act. Although the syntactic structure and verbal content of the poems place Sara in a state of derangement, it is the musical setting that is responsible for the instantaneous and overwhelmingly raw portrayal of Sara’s madness. This paper explores the use of fragmentation, non-linearity, musical fixation, and dissonance to musically represent Sara’s madness.